Intelligently Designed : How Creationists Built the Campaign against Evolution - Caudill, Edward (Book collections on Project MUSE., 2013)
"Tracing the growth of creationism in America as a political movement as opposed to a science-religion issue, this book explains why anti-evolution, this peculiarly American phenomenon, has succeeded, as measured in terms of popular appeal. Conceiving the history of creationism as a strategic public relations campaign, it emphasizes ways that media have been used to spin creationism as a viable, even preferable, alternative to evolution. Understanding creationists' campaigns means understanding their popularity and appeal in American culture. Beginning with the rise of fundamentalism in the early 20th century, Edward Caudill traces the movement through the rest of the 20th and into the 21st century. He illustrates how the 1925 Scopes trial created the contours of the modern debate over evolution. Its primary combatants--Clarence Darrow and William Jennings Bryan--became the celebrity representatives of opposing sides in the battle over teaching evolution in public schools. He then draws parallels between the media's role in the Scopes trial and subsequent political campaigns against evolution represented by Moral Majority of the 1980s, the 2005 cases in Kansas and Dover, PA, current anti-evolution politicians, such as Sara Palin and Mike Huckabee, and highlight creationism's recent gravitation toward museums and websites as a medium of communication. Caudill draws from media sources, trial transcripts, films, as well as the archives to highlight the importance of historical myth in popular culture, religion, and politics and situate this nearly century-old debate in American cultural history"--